Evaluation of a syndromic panel polymerase chain reaction (spPCR) assay for the diagnosis of device‐associated bone and joint infections (BJI). (March 2022) - Berneking, Laura; Haas, Michaela; Frielinghaus, Lisa; Berinson, Benjamin; Lütgehetmann, Marc; Christner, Martin; Aepfelbacher, Martin; Gerlach, Ulf; Seide, Klaus; Both, Anna; Rohde, Holger
Highlights: Molecular approaches may improve diagnostics in bone and joint infections (BJI). Comparison of two molecular assays with culture-based diagnostics in 126 BJI specimens. A syndromic panel PCR (spPCR) yielded a high diagnostic sensitivity. spPCR detected pathogens in negative BJI, thus being of potential clinical value. spPCR is an add-on diagnostic tool in BJI. Abstract: Objective: Pathogen detection is crucial for diagnosis and targeted therapy in implant-associated bone and joint infections (BJI). Culture-based microbiology regularly fails to identify causative pathogens. This study evaluated the diagnostic accuracy and clinical usefulness of a syndromic panel polymerase chain reaction (spPCR) assay targeting common BJI pathogens in tissue specimens from patients with implant-associated BJI. Methods: Results obtained by spPCR assay and a 16S rDNA PCR were compared with results obtained from a standard of care (SOC) culture-based diagnostics, serving as a gold standard. In total, 126 specimens obtained from 73 patients were analyzed. Results: The spPCR assay correctly identified 33/40 culture-positive samples (82.5 %) and was positive in 9/86 (10.5 %) culture-negative samples, resulting in an overall sensitivity of 84.6 % (95% confidence interval [CI] 68.79-93.59%) and specificity of 89.35% (95% CI 80.6-94.81%). The spPCR was more sensitive compared with the 16S rDNA PCR (37.5%). The spPCR identified pathogens in 7/51 (13.7%) SOC-negative patients. Re-evaluation of spPCR results in clinical context suggested their clinical significance. Conclusion: An spPCR assay targeting common pathogens causing implant-associated BJI may help to identify causative agents in culture-negative cases. As false-negative results are possible, spPCR assays appear as an add-on approach for pathogen detection in implant-associated BJI.